DEVELOPMENT OF STUDENT LEARNING OUTCOMES TEST INSTRUMENTS OF 11th GRADE HIGH SCHOOL ON SOUND WAVE MATERIAL - Ersano Ndruru; Sabani Sabani (IPER (Indonesian Physics Education Research), 2021)
Development of test instruments is the process of developing tools or procedures used in the framework of measurement and assessment activities. This study aims to develop well-qualified questions including validity, reliability, difficulty index, and differentiation. This research is a research and development with a development process using a 4D development model developed by Thiaragajan, et al (1974) covering four stages, i.e. : Define, Design, Development, and Disseminate, which in this study was only conducted up to 3D (development stage). The definition stage is performed student analysis, material analysis, and objective analysis. The design stage is the preparation of tests and the selection of test formats. The development stage consists of instrument preparation, expert validation and product trials to students. The test instruments developed are assessed according to the indicators and aspects of validation so that they are declared valid by the validator. The reliability value of the test instrument developed is 0.66 which belongs to the category of moderate reliability. Furthermore, the level of difficulty obtained is 8 medium questions and 2 easy questions, and the differentiation obtained is 7 enough questions and 3 good questions. The developed test instruments are acceptable and eligible to be used as test results of students' learning results on sound wave materials in grade 11 of high school.